Using the dog as a model to investigate environmental and genetic risk factors for mature, antigen-driven lymphoproliferative disorders - Labadie, Julia, author; Magzamen, Sheryl, advisor; Avery, Anne, advisor; Anderson, Brooke, committee member; Feigelson, Heather, committee member; Morley, Paul, committee member; Page, Rodney, committee member (Colorado State University. Libraries, 2017)
To view the abstract, please see the full text of the document.